Hallelujah junction : composing an American life - Adams, John, 1947- (New York : Farrar, Straus and Giroux, 2008)
An eminent composer shares the story of his life, from his childhood and early studies in classical composition to his minimalist and "docu-opera" achievements, in an account that evaluates his professional relationships and the social movements that inspired his creative process.
Winnipesaukee Gardens -- From Help to Let it be -- Free radicals -- Regal apparel -- Faulty wiring -- A harmony lesson -- The people are the heroes now -- Singing terrorists -- Mongrel airs -- The machine in the garden -- Technical difficulties -- How could this happen? -- A swirl of atoms -- Tree of life -- Garage sale of the mind.
Includes indexes.
Keywords: Adams, John, -- 1947-; Composers -- United States -- Biography